Estudio de factibilidad para la producción y comercialización del vino de verano artesanal, sabor a mora envasado en lata, en la Ciudad de Loja. - Cano Ortega, Verónica Lizbeth (2023)
This feasibility study focuses on analyzing the feasibility of producing and marketing artisan summer wine with blackberry flavor, packaged in a can, in the city of Loja. To achieve this, an exhaustive investigation is carried out, which used various methods, techniques and processes that facilitated its investigation, development and validation. The methods used included the descriptive and exploratory approach, and techniques such as surveys and interviews were used. The preliminary results reveal that within the market study, 369 surveys were applied to the economically active population (PEA) of the city of Loja between 20 and 54 years with favorable results where 84% of the surveyed population consume artisanal wine. 72% prefer blackberry-flavored wine and 97% of the population that consume blackberry- flavored artisanal wine state that they would be our customers, obtaining as a result a growing demand for artisanal products and a favorable receptivity towards innovative flavors. In the technical study, the size, location, requirements of the company and its production process were covered, establishing a production capacity of 68,751 350ml cans per year of artisan summer wine flavored with blackberry. The administrative study defined that the company will be a limited liability company called "VILCANITO. LTDA.". The financial study reveals that an own capital of $21,140.22 and an external capital of $16,760.15 are required, financed by BAN ECUADOR. The price of the product was established at $2.55 for our intermediaries for the first year of the project's life. The financial evaluation showed that the project is feasible, with a positive Net Present Value (NPV) of $50,759.51, an Internal Rate of Return (IRR) of 49.77%, a Cost Benefit Ratio (RBC) that indicates 15 cents of profitability for every dollar invested, and a Capital Recovery Period (PRC) of 2 years, 2 months and 0 days. The project's sensitivity to variations in costs and revenues also turned out to be low. Finally, the potential viability of the production and commercialization of artisanal summer wine with blackberry flavor, packaged in a can, in the city of Loja is demonstrated.